The Philosophical Basis of Al-Ahkam Al-Sulthaniyah and Its Relevance to The Indonesian Government Based on Asta Cita - Yudha, Gesit; Kesuma, Arsyad Sobby; Aziz, Abdul; Fauzan, Fauzan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
This study discusses the relevance of Islamic political principles proposed by Al-Mawardi in Al-Ahkam As-Sulthaniyyah for the context of the current Indonesian government and financial management. The method used in this study is a literature review with a heuristic analysis approach. The findings of this study indicate that al-Mawardi's thoughts in al-Ahkam al-Sulthaniyyah provide the philosophical foundations include the concepts of al-'Adl (justice), Amanah (moral responsibility), and maslahah (public welfare). Al-Mawardi's principles are in line with the Indonesian government system that prioritizes morality, people's welfare, and wise state governance. President Prabowo Subianto's Asta Cita vision, reflected in economic development, strengthening human resources, international cooperation, and industrial and infrastructure development, reflects Islamic moral values in realizing